Two analytical approaches quantifying the electron donating capacities of dissolved organic matter to monitor its oxidation during chlorination and ozonation. (1st November 2018) - Önnby, Linda; Walpen, Nicolas; Salhi, Elisabeth; Sander, Michael; von Gunten, Urs
Abstract: Electron-donating activated aromatic moieties, including phenols, in dissolved organic matter (DOM) partially control its reactivity with the chemical oxidants ozone and chlorine. This comparative study introduces two sensitive analytical systems to directly and selectively quantify the electron-donating capacity (EDC) of DOM, which corresponds to the number of electrons transferred from activated aromatic moieties, including phenols, to the added chemical oxidant 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulphonate) radical cation (i.e., ABTS + ). The first system separates DOM by size exclusion chromatography (SEC) followed by a post-column reaction with ABTS + and a spectrophotometric quantification of the reduction of ABTS + by DOM. The second system employs flow-injection analysis (FIA) coupled to electrochemical detection to quantify ABTS + reduction by DOM. Both systems have very low limits of quantification, allowing determination of EDC values of dilute DOM samples with <1 mg carbon per liter. When applied to ozonated and chlorinated model DOM isolates and real water samples, the two analytical systems showed that EDC values of the treated DOM decrease with increasing specific oxidant doses. The EDC decreases detected by the two systems were in overall good agreement except for one sample containing DOM with a very low EDC. The combination of EDC with UV-absorbance measurements gives further insights into the chemical reaction pathways of DOM with chemical oxidants such as ozone or chlorine. We propose the use of EDC in water treatment facilities as a readily measurable parameter to determine the content of electron-donating aromatic moieties in DOM and thereby its reactivity with added chemical oxidants. Graphical abstract: Highlights: Determination of electron-donating capacity (EDC) in DOM by two analytical methods. EDC is a quantitative measure of activated aromatic moieties in DOM, including phenols. High sensitivity of methods allows analysis of dilute DOM samples (<1 mgC ·L −1 ). Ozonation and chlorination results in dose- and oxidant-dependent EDC decreases. EDC provides a means to assess oxidant reactivity with DOM and adjust oxidant dosing.